Absorption and emission features of Ho3+ ion in Nb2O5 mixed Lithium zirconium silicate glasses. (2018) - Srikumar, T.; Srinivasa Rao, Ch.; Rao, M.C.; Raja Priyanka, R.; Vennela, T.; Saidurga, J.; Karthik, B.
Abstract: Li2 O–ZrO2 –SiO2 : Ho 3+ glasses mixed with Nb2 O5 were prepared. Optical absorption and photoluminescence spectra of these glasses have been recorded at room temperature. The optical absorption spectra of all glasses recorded at room temperature in the wavelength region 300-2000 nm exhibited several absorption bands all from the ground state 5 I8 to 5 G5, 5 G6, 5 F1, 5 F3, ( 5 F4 + 5 S2 ), 5 F5, 5 I5, 5 I6, 5 I7 . The luminescence spectra of all the glasses recorded at room temperature in the visible and NIR regions exhibited the following prominent emission bands 5 F3 → 5 I8, 5 S2 → 5 I8, 5 G4 → 5 I6, 5 K8 → 5 I7, 5 F5 → 5 I8, 5 G5 → 5 I6, 5 F4 → 5 I7, 5 G5 → 5 I5, 5 F2 → 5 I6, 5 F3 → 5 I6, 5 I5 → 5 I8 (Visible region) and, 5 I7 → 5 I8 (NIR region). The luminescence spectra of Nb2 O5 mixed Li2 O–ZrO2 –SiO2 glasses (free of Ho 3+ ions) have also exhibited broad emission band in the blue region. This band is attributed to radiative recombination of self-trapped excitons (STEs) localized on substitutionally positioned octahedral Nb 5+ ions in the glass network. The Judd–Ofelt theory was successfully applied to characterize Ho 3+ spectra of all the glasses. From this theory, various radiative properties like transition probability A, branching ratio β r, the radiative lifetime τ r, for 5 S2 emission levels in the spectra of these glasses has been evaluated. The radiative life time for 5 S2 level of Ho 3+ ions has also been measured and quantum efficiencies were estimated.